Influence of the deposition of sludge from sewage treatment on the emission characteristics of a landfill. Einfluss der Ablagerung von Schlaemmen aus der Abwasserreinigung auf das Emissionsverhalten eines Muellkoerpers - "Kruse, K"; "Kayser, R [Technische Univ. Braunschweig (Germany, F.R.). Inst. fuer Siedlungswasserwirtschaft]" (1991)
Sludge from sewage treatment accounts for an essential part of wastes dumped at sanitary landfills. In a model experiment, the emission characteristics of municipal waste alone, sewage sludge, and mixtures thereof were comparatively investigated. Both the leachate and landfill gas were investigated. The results were compared with measurements at landfills. Quite generally, an increase in the nitrogen concentration of leachate is to be expected. Lime-conditioned sewage sludges should be dumped as impervious lenses or cassettes. (orig.).
Keywords: "32 ENERGY CONSERVATION, CONSUMPTION, AND UTILIZATION"; "09 BIOMASS FUELS"; "SANITARY LANDFILLS"; "EMISSION"; "SLUDGES"; "WASTE DISPOSAL"; "CHEMICAL OXYGEN DEMAND"; "METHANE"; "PH VALUE"; "QUANTITATIVE CHEMICAL ANALYSIS"; "WASTE WATER"; "ALKANES"; "CHEMICAL ANALYSIS"; "HYDROCARBONS"; "HYDROGEN COMPOUNDS"; "LIQUID WASTES"; "MANAGEMENT"; "ORGANIC COMPOUNDS"; "OXYGEN COMPOUNDS"; "WASTE MANAGEMENT"; "WASTES"; "WATER"; "320604* - Energy Conservation, Consumption, & Utilization- Municipalities & Community Systems- Municipal Waste Management- (1980-)"; "090900 - Biomass Fuels- Processing- (1990-)"